INTERACCIÓN ENTRE TROGIDOS (COLEOPTERA: TROGIDAE) Y TORTUGAS MARINAS (REPTILIA: CHELONIIDAE) EN EL PACIFICO MEXICANO - Rosano Hernández, María C.; Deloya, Cuauhtémoc (Instituto de Ecología, A.C., 2002)
From 1987 to 2000, great embryo and hatchling mortality (>70%) of sea turtles (Lepidochelys) has been reported in the nesting beach La Escobilla, Oaxaca, México. The embryo death in this beach was attributed by some authors mainly to the egg predation by a beetle belonging to the family Trogidae. Taxonomic examination confirmed that the beetle at La Escobilla was Omorgus suberosus Fabricius. This species has been also reported in some other nesting beaches of the Pacific, but in none of the Atlantic Ocean. The present paper, based on the literature published about both Omorgus and marine turtles (Lepidochelys), describes the interaction between Omorgus and sea turtles, and discusses the predatory role of Omorgus suberosus. Based in our research, there was insufficient evidence to point O. suberosus as a predator especialist in turtle eggs; the beetle seems to be a highly efficient and facultative necrophagous- saprophagous organism.